Hubungan Pola Makan Dengan Kadar Gula Darah Ibu Hamil Di Puskesmas Sukorame Kota Kediri - Charisma, Frizka Dian; Rahmawati, Rahajeng Siti Nur; Kundarti, Finta Isti; Hardjito, Koekoeh (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2025)
Abstract Proper nutrition during pregnancy plays a vital role in maintaining stable blood glucose levels and preventing gestational diabetes. This study aimed to analyze the relationship between dietary patterns and blood glucose levels in pregnant women. An analytic observational study with a cross-sectional design was conducted over two months at Sukorame Public Health Center in Kediri City. A total of 45 pregnant women in their second and third trimesters were selected using consecutive sampling. Dietary intake was assessed using a 24-hour food recall method and compared with the Recommended Dietary Allowance (RDA). Blood glucose levels were measured two hours postprandially using a glucometer. The majority of participants had normal dietary intake and normal blood glucose levels. The Fisher-Freeman-Halton test revealed a statistically significant association between dietary patterns and blood glucose levels (p = 0.021), with a Cramér’s V value of 0.502, indicating a moderate strength of association. These findings underscore the importance of balanced energy intake in regulating blood glucose during pregnancy. Therefore, enhancing nutritional education for pregnant women is strongly recommended, and future research should consider additional variables such as body mass index (BMI), physical activity, and stress factors.